A note on risk aversion and labour market outcomes: further evidence from German survey data - Christian Pfeifer (Institute for the Study of Labor (IZA), 2008)
Using the large-scale German Socio-Economic Panel, this note reports direct empirical evidence for significant correlations between risk aversion and labour market outcomes (full-time employment, temporary agency work, fixed-term contracts, employer change, quits, training, wages, and job satisfaction).
urn:nbn:de:101:1-20080605183
Keywords: J01; 330; Employment; job search; human capital; risk aversion; wages; Arbeitsangebot; Karriereplanung; Risikoaversion; Arbeitsverhältnis; Arbeitslosigkeit; Arbeitsmobilität; Lohn; Arbeitszufriedenheit; Deutschland